Layered double hydroxides for industrial wastewater remediation: A review - Sarkar S.; Upadhyay C. (My University, 2025)
Tanneries and textile industries significantly impact aquatic ecosystems through the discharge of effluents containing heavy metals, dyes, and metal-resistant bacterial pathogens. This review examines the potential of layered double hydroxides (LDHs) for addressing these environmental challenges. It offers a comprehensive analysis of LDH morphology, synthesis techniques, and performance in wastewater remediation. LDHs are ionic lamellar hydroxides, containing two different metal cations in the main layers and anionic species in the interlayer, have attracted substantial research interest due to their ease of synthesis and unique properties. This review distinguishes itself by correlating various synthesis methods for LDHs directly with their efficacy in wastewater remediation, offering insights not typically covered in other reviews. Furthermore, the review explores the critical role of interlayer anions, such as carbonate and sulfate, in determining its influence in the structural, chemical, and physical properties of LDHs. It also addresses how modifications with graphitic carbon nitride (gC3N4) and graphene-based materials enhance LDH's performance by increasing surface area, delaying charge recombination, and improving adsorption and photocatalytic activity. he review evaluates the impact of these factors on the removal of pollutants from wastewater and provides an in-depth discussion of the mechanisms involved in pollutant removal, including adsorption, ion exchange, and photocatalysis. It also highlights the antibacterial properties of LDHs, particularly when combined with advanced materials, demonstrating their potential antimicrobial efficacy. In addition to presenting a fresh perspective on the correlation between synthesis methods and performance outcomes, this review offers a comprehensive overview of the limitations and challenges associated with LDH technologies. It provides valuable insights into the optimization process and practical considerations, making it an essential resource for advancing LDH technologies in real-world wastewater treatment applications. © 2024 Elsevier B.V.